KUALITAS PENGISIAN CATATAN PERKEMBANGAN PASIEN TERINTEGRASI TERHADAP PENGAMBILAN KEPUTUSAN KLINIS DI RUMAH SAKIT KEBONJATI - Mohamad Naufal Ramdhani; Sali Setiatin (Jurnal Infokes, 2026)
The completeness and accuracy of entries in the Integrated Patient Progress Notes (CPPT) serve as key quality indicators of medical records and play a crucial role in supporting clinical decision-making processes in hospitals. This study aims to examine how the quality of CPPT documentation relates to the accuracy of clinical decisions for inpatient care. A mixed-methods design was employed, consisting of a quantitative review of 360 inpatient Electronic Medical Records (EMR) and in-depth interviews with two nursing staff. The findings revealed an overall CPPT completion rate of 49.44%, with substantial variation across units, ranging from 21.95% in Mawar to 82.14% in Cempaka 2. The qualitative analysis generated four central themes: high workload, limitations in health information technology infrastructure, the need for continuous training, and the role of managerial supervision. Integrated analysis showed that units with stronger supervision and more intensive training demonstrated higher CPPT completeness. These results indicate that the quality of CPPT documentation influences the effectiveness of clinical decision-making. Therefore, improving documentation quality requires multidimensional interventions, including strengthening healthcare worker competencies, enhancing information technology infrastructure, and ensuring consistent supervisory practices.